Analysis of the FACTS devices impact on the transmission line protection operation; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Ruban N. Yu. Nikolay Yurievich; Gusev A. S. Alexander Sergeevich; Bay Yu. D. Yuly Dmitrievich; Razzhivin I. A. Igor Andreevich (2021, 2021)
Title screen